Optimization of Feed Locations for Double-feed Columns Based on the Column Grand Composite Curve. (May 2017) - Liu, X.G.; He, C.; He, C.C.; Zhang, B.J.; Chen, Q.L.
Abstract: In this work, a novel graphical method is presented to quantitatively identify the optimal feed stage locations of double-feed columns on the basis of the column grand composite curve (CGCC). A double-feed column can be composed of two simple single-feed columns under minimum thermodynamic conditions according to previous research. Then, two material and enthalpy balance envelopes are regulated according to the feed locations of the simple column from the top down. Subsequently the whole simple column is regarded as entire-rectifying and entire-stripping sections to generate the theoretical temperature-enthalpy curves, which are termed as entire-rectifying and entire-stripping curves. Finally, the entire-rectifying and stripping curves of the two simple columns can be combined into three theoretical curves, namely overall entire rectifying, intermediate, and stripping curves. Then, a quantitative approach is proposed to determine the appropriate feed locations of the double-feed columns. By investigating the relationship between the feed points of the CGCC and the intersections of the three theoretical curves, the optimal feed locations can be identified when the enthalpy differences obtained from the CGCC and the theoretical curves reach minimum at each stage. It is found that the appropriate feed stages of a double-feed column are positions which are closest to the intersection points. As a case study, a binary double-feed column is simulated to demonstrate the accuracy and rationality of the graphical method. By optimizing feed locations, the cold and hot utility requirements of the column were reduced by 43.9% and 46.9%, respectively.